Microbial degradation of n-alkyl tetrahydrothiophenes found in petroleum. - Fedorak, P M (1988)
Although n-alkyl-substituted tetrahydrothiophenes are found in nonbiodegraded petroleums, they are not found in petroleums which have undergone biodegradation in their reservoirs. These observations suggested that this group of compounds with alkyl chain lengths from approximately C10 to at least C30 is biodegradable. Two of these sulfides, 2-n-dodecyltetrahydrothiophene (DTHT) and 2-n-undecyltetrahydrothiophene, were synthesized, and their biodegradabilities were tested by using five gram-positive, n-alkane-degrading bacterial isolates. The alkyl side chains of these compounds were oxidized, and the major intermediates found in 2-n-undecyltetrahydrothiophene- and DTHT-metabolizing cultures were 2-tetrahydrothiophenecarboxylic acid (THTC) and 2-tetrahydrothiopheneacetic acid (THTA), respectively. Four n-alkane-degrading fungi were also shown to degrade DTHT, yielding both THTA and THTC. Quantitation of tetrahydrothiophene ring-containing products in 28-day-old bacterial and fungal cultures suggested that THTC and THTA were metabolized further to unidentified products. In addition, two of the bacterial isolates were shown to degrade a mixture of n-alkyl tetrahydrothiophenes isolated from Bellshill Lake crude oil.